Computational investigation of the comparative analysis of cylindrical barns subjected to earthquake - Zandi, Yousef; Shariati, Mahdi; Marto, Aminaton; Wei, Xing; Karaca, Zeki; Dao, Duykien; Toghroli, Ali; Hashemi, Mir Heydar; Sedghi, Yadollah; Wakil, Karzan; Khorami, Majid (Techno-Press, 2018)
The structural behaviors of cylindrical barns as a specific engineering structure have been considered as a complicated computing process. The structure design against the earthquake load, to protect by using the code, is an urgency avoiding unexpected damages. The situation has been subjected to the applied design method if there would be no failure across the construction procedures. The purpose of the current study is to clarify the behaviors of cylindrical reinforced concrete barns through the analytic methods across the mass and Lagrangian approaches through the whole outcomes comparison indicating that the isoparametric element obtained from the Lagrangian approach has been successfully applied in the barns earthquake analysis when the slosh effects have been discarded. The form of stress distributions is equal with sz closed distributions to one another.